2018
DOI: 10.1038/s41378-018-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

0.04 degree-per-hour MEMS disk resonator gyroscope with high-quality factor (510 k) and long decaying time constant (74.9 s)

Abstract: The disk resonator gyroscope is an attractive candidate for high-performance MEMS gyroscopes. This gyroscope consists of a sensor and readout electronics, and the characteristics of the sensor directly determine the performance. For the sensor, a high-quality factor and long decaying time constant are the most important characteristics required to achieve high performance. We report a disk resonator gyroscope with a measured quality factor of 510 k and decaying time constant of 74.9 s, which is a record for ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…In the present study, the CVG with an optical readout was found to exhibit a bias instability of <0.5° h −1 , which is a factor of ~50 lower than the performance of 0.01° h −1 for state-of-the-art gyroscopes. For example, a MEMS disk resonator gyroscope 40 was recently shown to have a bias instability of <0.04° h −1 with a long decay time of 74.9 s. This impressive performance for a MEMS gyroscope requires complex mechanical structures with a nontrivial fabrication process. The fabrication of the CVG structures we report in this work are relatively simple, and since the sensitivity of the optical readout can be substantially improved, we expect that in future studies, the performance of the CVG described here will also be improved.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the CVG with an optical readout was found to exhibit a bias instability of <0.5° h −1 , which is a factor of ~50 lower than the performance of 0.01° h −1 for state-of-the-art gyroscopes. For example, a MEMS disk resonator gyroscope 40 was recently shown to have a bias instability of <0.04° h −1 with a long decay time of 74.9 s. This impressive performance for a MEMS gyroscope requires complex mechanical structures with a nontrivial fabrication process. The fabrication of the CVG structures we report in this work are relatively simple, and since the sensitivity of the optical readout can be substantially improved, we expect that in future studies, the performance of the CVG described here will also be improved.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, peculiar phenomena, including grain boundary sliding 9 and crystal twinning 10 , can be directly observed under torsion. In addition, various devices, including micromirrors 11 , MEMS gyroscopes 12 , microturbines 13 , and biomedical devices 14 , are subjected to torsional stress during operation, making torsional analysis an essential method for material evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…As a new generation gyroscope, the micro-electro-mechanical system disk resonator gyroscope (MEMS DRG) is an attractive candidate for high-performance MEMS gyroscopes due to its near navigational grade precision and small volume [ 1 , 2 , 3 , 4 , 5 ]. As a solid wave gyroscope (SWG), MEMS DRG inherently possesses a high Q factor and mode match mechanism, which maintain its low mechanical-thermal noise and high mechanical sensitivity [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%